Is closing the agricultural yield gap a “risky” endeavor? - Gatti, Nicolas; Cecil, Michael; Baylis, Kathy; Estes, Lyndon; Blekking, Jordan; Heckelei, Thomas; Vergopolan, Noemi; Evans, Tom (Elsevier, 2023)
CONTEXT: Sub-Saharan Africa (SSA) has the climatic and biophysical potential to grow the crops it needs to meet rapidly growing food demand; however, agricultural productivity remains low. While potential maize yields in Zambia are 9 t per hectare (t/ha), the average farmer produces only 1–2. OBJECTIVE: We evaluate the contribution of responses to weather risk to that gap by decomposing the yield gap in maize in Zambia. While we know that improved seed and fertilizer can expand yield and profit, they may also increase the variance of yield under different weather outcomes, reducing their adoption. METHODS: We use a novel approach combining crop modeling and statistical analysis of survey data to obtain the yield gap components in Zambia driven by input cost and input risk. We use a crop model to simulate district-level marginal effects of fertilizer and seed maturity choice on the mean and variance of expected yield and profit under all-weather outcomes for each district for the past 30 years. We compare input levels that maximize expected yield to those that maximize expected profit and maximize the expected mean-variance trade-off assuming risk-aversion. To determine how much farmers' input choices are made to reduce risk, we then quantify differences in the expected riskiness of inputs by district. RESULTS AND CONCLUSIONS: We find approximately one-quarter of the yield gap can be explained by risk-reducing behavior, albeit with a substantial geographic variation. Given this finding, under present conditions, we expect that the average maximum yield that farmers can obtain without increasing risk is 6.75 t/ha compared to a potential profit-maximizing level of 8.84 t/ha. SIGNIFICANCE: The risk-related yield gap is only expected to increase with weather extremes driven by climate change. Promoting “one-size-fits all” solutions to closing the yield gap could underestimate the effect of risk mitigation on agricultural production while increasing farmers.